Carbon molecule gasifier - CAO YING; YUN MINGYUE; LI JIAN; ZI YUEBIN (2017)
The utility model relates to a coal gas production equipment, especially a carbon molecule gasifier. Including the furnace body, the furnace body bottom is equipped with the firegrate, the furnace body is the toper structure. The furnace body is the toper structure, increased between the gas -solid reaction thing the first time direct contact the interface for stove internal oxidation reaction, it is more complete that the reaction of combustion who makes carbon goes on, gasification intensity is high, the caloric power of gas is high, the lime -ash phosphorus content is low, environmental protection and energy saving have improved the quality and the output of coal gas. 本实用新型涉及煤气生产设备，尤其是种碳分子气化炉。包括炉体，炉体底部设有炉篦，所述炉体为锥形结构。炉体为锥形结构，增大了气固反应物之间的第次直接接触的界面，加快了炉内氧化反应，使碳的燃烧反应进行的更加完全，气化强度高，煤气热值高，灰渣含碳量低，环保节能，提高了煤气的质量和产量。